Penerapan Pembelajaran Berbasis Masalah dalam Meningkatkan Sikap Kepedulian Lingkungan Siswa - Haryati, Wanis; Widyantari, Rima; Lestari, Sofiana; Afif, Hanan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
This research was conducted on the basis of concern for the behavior of people who seem indifferent to environmental problems that occur in the surrounding environment, as well as the hope to form a younger generation who cares and has better environmental ethics. This study aims to determine the effectiveness of problem-based learning in increasing students' environmental awareness, especially in cases of global environmental problems. This research method uses Quasi Experimental with One Group Pretest-Posttest Design and purposive sampling. The data was obtained through an attitude scale of environmental concern based on the level of attitude domain according to Krathwohl, Bloom, and Masia. The results show that the problem-based learning model through the use of global environmental problems is effective in increasing students' environmental awareness. This is indicated by the gain index value of 0.52 which is included in the medium category and the average attitude value is above the Minimum Completeness Criteria (KKM) which is 81.4. The environmental awareness attitude indicator that has the highest value is caring or aware with a value of 95, and the lowest is commitment with a value of 55. The results of this study are expected to be implemented in daily learning activities to familiarize students with caring and good character. to the surrounding environment.